Effects of Interactivity between Audience and Urban Advertisement - Manavirad, Mitra; Samadzadeh, Mahsa (Journal of History Culture and Art Research, 2017)
Nowadays, advertisement plays an important and impressive role in our lives and we are witnessing different works in this field. The emergence of new technologies in this field has led to the arrival of a new style of advertising with different interactivity and administrative functions. Interactive advertising is considered as one of the most up to date urban advertising. With regard to the arrival of this new style of advertising and using them in different countries, this research investigates the effectiveness of an advertisement’s interaction with the audiences in urban advertising through a descriptive/analytical approach as well as field study with regard to the type of advertising usage including commercial, promotional, educational, social etc. It is assumed that an interactive advertising confronts the audience with many challenges and makes him from a static and watching audience to an actor and explorer audience. In such advertisements, the audience enters a path with interactivity where the advertisement guides him and audience responses positively to this action; after a simple activity and in some cases, he interacts and communicates with the advertisement just by passing by it. In interactivity advertisements in urban spaces, the artist pays much attention to audience participation for challenges or performing specific activity that will lead to a result. The use of interactive advertising in various forms such as billboards, stands, and advertisements at bus stops and so on has increased in recent years, developed countries, and countries that are more familiar to technologies. These works are considered a new step in the field of urban advertising. This research selects samples of using such creative advertisements, especially in commercial areas in different countries as well as Iran. It considers the producing method, ideation, and effectiveness of each in a specific period as well as their installation and commissioning places. The results emphasize on more effectiveness of interactive advertising as well as more contribution of audiences in the process of advertising in comparison to simple and non-interactivity advertising.